2016
DOI: 10.2147/cpt.s84855
|View full text |Cite
|
Sign up to set email alerts
|

Biological rhythms and fertility: the hypothalamus–pituitary–ovary axis

Abstract: In addition to normal physiological processes, a number of pathological conditions exhibit diurnal and seasonal fluctuations in their incidence. These biological rhythms are genera ted by the circadian clocks that adjust their functions and adapt to the habitat. Misalignment of biological rhythms and disrupted functions of the circadian clocks may eventually have a negative impact on reproduction, which is the focus of this review. A large body of literature from animal studies has demonstrated the role of cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…Of the traits we tested, we found some evidence that being a morning person may result in a younger age at last childbirth and a reduced risk of multiple pregnancy losses, schizophrenia and depression. Although these results need replication, there is existing evidence of the relationship between circadian rhythms and fertility in women [43][44][45] , and between circadian rhythms and mental health suggesting that this an area for further investigation.…”
Section: Discussionmentioning
confidence: 89%
“…Of the traits we tested, we found some evidence that being a morning person may result in a younger age at last childbirth and a reduced risk of multiple pregnancy losses, schizophrenia and depression. Although these results need replication, there is existing evidence of the relationship between circadian rhythms and fertility in women [43][44][45] , and between circadian rhythms and mental health suggesting that this an area for further investigation.…”
Section: Discussionmentioning
confidence: 89%
“…Suprachiasmatic nucleus of the hypothalamus is known as a master clock as it contains the largest amounts of circadian proteins PERIODS, CRYPTOCHROME, BMAL1, and CLOCK [25]. These proteins are also present in peripheral tissues in the body, where they regulate the timing and oscillation of gene expressions and biological events.…”
Section: Discussionmentioning
confidence: 99%
“…Yamazaki et al [24] reported that suprachiasmatic nucleus rapidly adjusts to light shifts, but peripheral tissues shift more slowly. For example, PER2 expression in the ovary peaks at light offset delayed by 4-6 hours relative to its expression in the suprachiasmatic nucleus [25]. Also, the duration of light exposure determines whether there will be shifts in the circadian rhythm in both humans and animals [26].…”
Section: Light Pollution and Photic Stressmentioning
confidence: 99%
See 1 more Smart Citation